The Impact of Friendship in the Workplace on Job Commitment: A Field Study in Private Sector Automotive Companies in Saudi Arabia - Ali, Ahmed Farouk (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aims to explore the impact of friendship relationships between managers and subordinates on job engagement levels in the private automotive sector in Saudi Arabia. The significance of the research lies in highlighting the dual effects of these relationships; while friendships can enhance commitment and job satisfaction by providing emotional support and professional assistance, they may also lead to negative outcomes, such as unjust decisions made to avoid accusations of favoritism, thus impacting organizational justice. The study adopts a descriptive-analytical approach to examine the following hypotheses: the existence of a positive relationship between workplace friendships and job engagement, the positive impact of friendships on job satisfaction and organizational commitment, and their negative influence on managerial decisions regarding promotions and rewards. The findings indicate that the impact of workplace friendships is dual-faceted: positive when managed under organizational policies that promote justice and negative when biases affect the objectivity of administrative decisions. Furthermore, the study reveals differing effects between new employees and experienced ones. The study concludes by emphasizing the importance of developing policies and procedures that balance building friendly workplace relationships with maintaining professionalism and transparency. It also highlights the need for training programs for managers on managing professional relationships, contributing to enhancing justice and trust within the work environment.
Keywords: Workplace friendship; job engagement; organizational justice; managerial bias; professional relationships; managerial leadership; institutional transparency